Cytosolic CTP Production Limits the Establishment of Photosynthesis in Arabidopsis - Bellin, Leo; Scherer, Vanessa; Dörfer, Eva; Lau, Anne; Vicente, Alexandre Magno; Meurer, Jörg; Hickl, Daniel; Möhlmann, Torsten (Frontiers in Plant Science, 2021)
CTP synthases (CTPS) comprise a protein family of the five members CTPS1-CTPS5 in Arabidopsis, all located in the cytosol. Specifically, downregulation of CTPS2 by ami-RNA technology results in plants with defects in chlorophyll accumulation and photosynthetic performance early in development. CTP and its deoxy form dCTP are present at low levels in developing seedlings. Thus, under conditions of fast proliferation, the synthesis of CTP (dCTP) can become a limiting factor for RNA and DNA synthesis. The higher sensitivity of ami-CTPS2 lines towards the DNA-Gyrase inhibitor ciprofloxacin, together with reduced plastid DNA copy number and 16S and 23S chloroplast ribosomal RNA support this view. High expression and proposed beneficial biochemical features render CTPS2 the most important isoform for early seedling development. In addition, CTPS2 was identified as an essential enzyme in embryo development before, as knock-out mutants were embryo lethal. In line with this, ami-CTPS2 lines also exhibited reduced seed numbers per plant.